Ichnocoenoses from the Carboniferous of eastern Canada and their implications for the recognition of ichnofacies in nonmarine strata - Keighley, Dave; Pickerill, Ron (Atlantic Geology)

(untitled) (The Electronic Text Centre at the University of New Brunswick Libraries, 2003)
ABSTRACT Sixty-six suites of trace fossils from thirty-four different localities were collected or observed in the Carboniferous Mabou and Cumberland groups of western Cape Breton Island. Recurrent suites have been compiled into thirteen ich-nocoenoses. Twelve of these ichnocoenoses, together with others from the Carboniferous elsewhere in the Maritimes, can be considered representative of two revised ichnofacies and their related composite ichnofacies. The remaining ichnocoenosis is currently anomalous. In our view, some ichnofacies identified in the nonmarine realm have been too broadly defined. They allow for the inclusion of ichnocoenoses that are better considered representatives of composite ichnofacies. The Mermia ich-nofacies is thus emended to consist primarily of systematic-coverage interface burrows and trails, irregular interface burrows and trails, non-striate pits, sinusoidal burrows and trails, migrating burrows, systematic-coverage burrow networks, (dense coverage) simple burrows and, if present, subordinate trackways. It remains an ichnofacies indicative of quiet water, oxygenated, permanently subaqueous conditions with significant organic input. Two Cape Breton Island ichnocoenoses are representative of the revised Mermia ichnofacies. The Scoyenia ichnofacies is emended to consist primarily of bilobate or striate pits and trails, trackways, meniscate burrows, (sparse coverage) simple burrows and, if present, subordinate vertical burrows. It remains an ichnofacies indicative of transitional environments, spe-cifically quiet water conditions that regularly dry out, or periodically inundated floodplains. Four Cape Breton Island ichnocoenoses are representative of the revised Scoyenia ichnofacies. Six ichnocoenoses from Cape Breton Island contain some trace fossils considered typical of both the Mermia and Scoyenia ichnofacies as emended. Two interpretations are possible. These ichnocoenoses might indicate instances where the trace-fossil producers were environmentally tolerant animals that could inhabit and behave similarly in either setting. Alternatively, they may represent cases where producers active in different environments had their traces juxtaposed or even overprinted due to a change in environmental conditions. In this latter case, the ichnocoenoses can be considered examples of composite ichnofacies that are taphonomic successors of combinations of the Mermia, Scoyenia, and the well-established Skolithos ichnofacies.